Herbal extracts exhibit anti-diabetic activities in 3T3-L1 adipocytes model - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Taher, Muhammad; Ichwan, Solachuddin Jauhari Arief (Progress in Nutrition, 2015)
The prevalence and suffering of diabetes and obesity has been increasing among the various communities of the world including Malaysia. The cost of treatment is also rising. Therefore, it is important to explore non pharmacological regimens that are non-invasive and with less health risks and cost burden to the patients, healthcare professionals and nations. The objective of this study was to evaluate efficacy of the traditionally used antidiabetic herbs. Methods: Water extracts of Andrographis paniculata, Lagerstroemia speciosa and Orthosiphon stamineus (Cat whisker) were prepared and evaluated for their effects on cell proliferation, adipogenesis, glucose uptake, quantification of mRNAs for Ppary, Glut4, adiponectin and leptin using Real-Time Polymerase Chain Reaction (qRT-PCR) in 3T3-L1 preadipocytes. Result and Discussion: There were significant (P